Implementing Derivative Tools As Foreign Exchange Risk Management for Steel Industries in Import Activiti - Sudipta, Haga; Wiryono, Sudarso Kaderi (Journal of Business and Management, 2012)
This paper examines implementation of using derivative tools which are forward and call options for steel industries in Indonesia. Steel industries in Indonesia depend on importing such commodities and raw materials to fulfill the high consumption because local production is not enough. Therefore, importing which needs forex will face risk in forex itself. The implementation of both tools are described in three different scenario of hedging percentage which are 25:75, 50:50, and 75:25. The results of this study will be as recommendation to steel industries in Indonesia to import raw materials in four months ahead with best toolPurpose: This study has purpose to help steel industries in controlling foreign exchange risk based on its high fluctuation while importing raw materials.Design/methodology/approach: The researcher did data gathering from primary data which is obtained from a representative company of steel and secondary data from the internet. Researcher also provide rule of each methods which is given by a commercial bank.Findings: Using call options is better than forward from expected values consideration with specification from the same bank who provide the tools.Research limitations/implications (if applicable): Only limited in over-the counter derivative which are call options and forward.Originality/value: Direct comparison between call option and forwardKeywords: Derivative, over-the counter, foreign exchange riskCategory: Finance